2012
DOI: 10.1089/tmj.2011.0081
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Physicians' Acceptance of Hospital Information Systems in Taiwan

Abstract: The findings of this study can help managers understand the key considerations affecting HIS development and use and provide important reference material for system improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…The stakeholders involved in online dental learning from nine countries were invited to complete the online Survey of Barriers in Online Learning Education in Health Professional Schools (SBOLEHPS). This survey was developed by the authors to cover aspects of known barriers in the literature (6): support (including financial) and resources (12,13,18,23), developmental issues and concerning the online learning tool itself (14,15,18), concerning the end-users (11,16,18,19), faculty attitudes and barriers (23-25), and cognitive abilities (i.e. computer self-efficacy) (13).…”
Section: Methodsmentioning
confidence: 99%
“…The stakeholders involved in online dental learning from nine countries were invited to complete the online Survey of Barriers in Online Learning Education in Health Professional Schools (SBOLEHPS). This survey was developed by the authors to cover aspects of known barriers in the literature (6): support (including financial) and resources (12,13,18,23), developmental issues and concerning the online learning tool itself (14,15,18), concerning the end-users (11,16,18,19), faculty attitudes and barriers (23-25), and cognitive abilities (i.e. computer self-efficacy) (13).…”
Section: Methodsmentioning
confidence: 99%
“…Several articles have reported on the technological component of telehealth, including infrastructure, support personnel, and information technology highways. 76–79 Data on implementation research, focusing on whole telehealth systems rather than individual technological components, are still sparse. 61 …”
Section: Teleresearchmentioning
confidence: 99%
“…The same relationship was positive and signi cant in Tubaishat's (2017) study, which applied TAM to investigate nurses' use behavior of an EHR system. Similarly, many studies have con rmed this relationship from physicians' perspective, such as studies by Alsharo et al (2019), Chen and Hsiao (2012), and Yarbrough and Smith (2007). In addition, a study conducted by Or et al (2011) to examine home-care patients' acceptance of a web-based and interactive self-management technology revealed that PEOU did not directly affect the BI, but it had a signi cant impact on PU.…”
Section: Discussionmentioning
confidence: 92%
“…A HIS is de ned as "a comprehensive, integrated information system designed to manage the administrative, nancial and clinical aspects of a hospital. It aims to achieve the best possible support of patient care and administration by electronic data processing" (Ismail et al, 2010, p. [16][17][18][19][20][21][22][23][24]. A HIS can also be de ned as "an information system that performs the function of processing data, information and knowledge in the secondary and tertiary healthcare levels" (Lee et al, 2011(Lee et al, , p. 2129(Lee et al, -2140.…”
Section: Introductionmentioning
confidence: 99%